GENETIC VARIATION OF cDNA OF LDLR GENE IN HYPORESPONDER CYNOMOLGUS MACAQUES (Macaca fascicularis) - Achmad Taher; Dedy Duryadi Solihin; Sulistiyani Sulistiyani; Dondin Sajuthi; Dewi Apri Astuti (Jurnal Kedokteran Hewan, 2017)
The study aimed to identify genetic variation of cDNA sequence from low density lipoprotein receptor (LDLR) gene of hyporesponder cynomolgus macaques. The animal used in this study was one hyporesponder cynomolgus macaque obtained from selection result in Primate Research Center-Bogor Institute of Agriculture (PSSP IPB). Amplification of cDNA from LDLR gene was performed using polymerase chain reaction (PCR) method with 4 pairs of walking primer. Alignment of amplification result sequence from 4 pairs of walking primer generated target sequence of 2353 bp which located on position 188-2540. Analysis of target sequence alignment on reference sequence in GenBank found 8 single nucleotide polymorphism (SNP), namely c408CT; c.1200CT; c.1497CT; c.1644TC; 1791TC; 1804AG; 2088CT; and 2377GA. Of 8 SNPs, c.1804AG and 2377GA. Two SNP (c.1804AG; dan 2377GA) caused changing of amino acids composition namely p.K602E (lysine → glutamate) and p.V793I (valine → isoleucine). This result proved the potential use of genetic variation of cDNA sequence from LDLR gene as genetic marker for selection of hyporesponder cynomolgus macaques.